2011
DOI: 10.1364/ao.50.003296
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally selective reflector surfaces for heat reduction in concentrator solar cells: modeling and applications of TiO_2:Nb-based thin films

Abstract: The energy conversion efficiency of a conventional pn junction solar cell decreases as the temperature increases, and this may eventually lead to failures in the photovoltaic system, especially if it uses concentrated solar radiation. In this work, we show that spectrally selective reflector (SSR) surfaces can be important for reducing the heat buildup on passively cooled solar cells. We outline a computational scheme for optimizing DC magnetron-sputtered TiO 2 :Nb-based SSRs tailored for silicon solar cells a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Invar Hamberg (1984) in his thesis (Ivar, 1984), reported that for the material to be used as spectrally selective coating material, it must meet three conditions: (1) should have a significantly wide band gap in order for the material to guarantee the key absorption edge to be below a solar wavelength length of approximately 300nm; (2) a prospect to dope the material to attain a high free carrier concentration leading to a high infrared reflectivity; (3) a limited absorption between the key absorption edge and the plasma wavelength, to guarantee a high luminous transmittance. Also, Maghanga in his thesis (Maghanga, 2009) reported separately that for a material to be used as a spectrally selective reflector (SSR), it must exhibit very high visible transmittance and high infrared reflectance. Furthermore, he suggested that the region of the plasma absorption peak must be positioned in the part of the solar spectrum with photon energies lower than the bandgap of the given solar cell.…”
Section: --mentioning
confidence: 99%
“…Invar Hamberg (1984) in his thesis (Ivar, 1984), reported that for the material to be used as spectrally selective coating material, it must meet three conditions: (1) should have a significantly wide band gap in order for the material to guarantee the key absorption edge to be below a solar wavelength length of approximately 300nm; (2) a prospect to dope the material to attain a high free carrier concentration leading to a high infrared reflectivity; (3) a limited absorption between the key absorption edge and the plasma wavelength, to guarantee a high luminous transmittance. Also, Maghanga in his thesis (Maghanga, 2009) reported separately that for a material to be used as a spectrally selective reflector (SSR), it must exhibit very high visible transmittance and high infrared reflectance. Furthermore, he suggested that the region of the plasma absorption peak must be positioned in the part of the solar spectrum with photon energies lower than the bandgap of the given solar cell.…”
Section: --mentioning
confidence: 99%
“…In the ideal case, these photons are those ones that can be converted to electrical power, whose energy is higher than the bandgap (E G ). Below bandgap energy photons are therefore reflected back towards the light source [11].…”
Section: Theoretical Modelmentioning
confidence: 99%
“…In this case, the aim is not to use the whole spectrum by PV cells, but to reduce undesirable heating. For example, Maghanga et al [76] introduced a cut-off mirror made of a layer of TiO 2 :Nb and a layer of Al 2 O 3 deposited on a substrate of aluminium. This mirror reflects 75.6% and 28% of sunlight below and above 1100 nm (near the band gap of Si), respectively.…”
Section: Spectral Splitting In Hybrid Receiversmentioning
confidence: 99%